Unicompartmental knee arthroplasty in patients with full versus partial thickness cartilage loss (PTCL): equal in clinical outcome but with higher reoperation rate for patients with PTCL - Maier, Michael Wolfgang; Kuhs, Felix; Streit, Marcus R.; Schuhmacher, Peter; Walker, Tilman; Ewerbeck, Volker; Gotterbarm, Tobias (Archives of orthopaedic and trauma surgery, 2015)
PurposeWhile the classical indications and contraindications for unicondylar knee arthroplasty (UKA) are widely accepted there is not yet consensus if patients with partial thickness cartilage loss (PTCL) are equally suited for treatment with UKA. The aim of our study was to determine if patients with partial thickness cartilage loss do equally well after treatment with UKA.MethodsThe study retrospectively analyzed the clinical results as well as the survival rates of 64 patients treated with UKA with the medial Oxford knee system. 32 patients had shown PTCL on preoperative radiographs, while the matched control group presented with full thickness cartilage loss (FTCL) medially. Outcome parameters were the Oxford Knee Score (OKS), the American Knee Society Score (AKS), and radiographic analysis.ResultsPostoperative improvement in OKS was 16 (SD 9.0) for patients with PTCL and 17 (SD 8.1) for patients with FTCL. There were no significant differences in the clinical scores between the two groups. Five Patients with PTCL had reoperation whereas there were only two in the bone on bone group. Cumulative survival at 5 years for all revisions was 84 % (95 % CI 72-92 %) for the PTCL group and 97 % (95 % CI 92-100 %) for the FTCL group. This difference was not yet significant (log rank: p = 0.095).ConclusionsPatients with PTCL are not equally suited for treatment with UKA like patients with bone on bone. Although PTCL has equal clinical results, it was associated with higher revision rates in our series.
Gesehen am 21.02.2017